Dynamics of non-newtonian oscillator - L. Yu. Martynov; E. S. Savin (Тонкие химические технологии)
For an explanation of curves of rotation of spiral galaxies the changed form of the second law of Newton is offered. For the purpose of possible experimental registration in terrestrial conditions of the changed law the model of non-newtonian oscillator is offered. Precisely and in various approximations the task about oscillations of non-newtonian oscillator is solved.